TRANSFORMATION OF THE IDEOLOGY IN CINDERELLA BY CHARLES PERRAULT INTO THE MOVIE BY KAY CANNON - Vincentia Sekar Arum; Supiastutik Supiastutik; Imam Basuki; Eko Suwargono (JEELL (Journal of English Education, Linguistics and Literature), 2025)
All literary creations are engaged with ideology because a literary creator always comes with an ideology. This research aims to identify the shift of ideology of patriarchy in the Cinderella fairy tale by Charles Perrault into feminism in the movie by Kay Cannon. The research method utilized is descriptive qualitative, and the data consists of narrative text from the fairy tale and visual scenes from the movie adaptation. The data is then compared and analyzed using Barthes' semiotics theory. In addition, through the shift of the ideologies, the motives of the adaptation are uncovered based on Hutcheon's theory of adaptation. The novelty of this research lies in the theory of adaptation utilized in the study. The findings show the ideology portrayed in the fairy tale is patriarchy, which is displayed in the characterization of Cinderella's subservience and the plot's resolution, which emphasizes male primogeniture. Conversely, the movie adaptation shows liberal feminism depicted by Cinderella and Gwen, the original characters of the movie, portraying their respective endeavor to achieve equality in economic and political spheres. The movie's resolution depicts liberal feminist ideals, in which the king acknowledges and appoints Gwen to rule the kingdom. The motives concluded from the ideologies include cultural capital and personal and political motives. The cultural capital motive highlights the value of adaptation work that utilizes patriarchy and feminism as cultural phenomena ingrained in society. The second motive, personal and political, emphasizes the adaptor, Kay Cannon's agenda on female empowerment, represented by Cinderella and Gwen.